THE IMPLEMENTATION OF RELIGIOUS MODERATION VALUES IN STATE MADRASAH ALIYAH KEEROM PAPUA - amri, amri (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2022)
This study aims to explain the values of religious moderation applied in StateMadrasah Aliyah (MAN) Keerom Papua. State Madrasah AliyahKeerom is an islamic school located in the midst of the majority Christianpopulation of Papua Province. However, the existence of Madrasah AliyahKeerom has never been disturbed. In fact, the school welcomes non-Muslimswho join to study in this school. This research uses a qualitative approach.The data were collected through interview, field observations anddocumentation. The results show that there are islamic moderation values thatare applied at State Madrasah Aliyah Keerom, namely the attitude ofcooperation between religious adherents in the madrasah environment (al-musawah), fairness (tawazzun), tolerance (tassamuh) and openness(tathawwur wa ibtikar).